SHOULD OBSOLESCENCE BE SEPARATELY ACCRUED? - Moyer, C. A. (The Accounting Review, 1940)
Abstract Accountants are just beginning to develop a consciousness of some of the problems of obsolescence that are present in connection with the use of fixed assets. This article is limited to consideration of only one question, which arises, that of separate accrual. Depreciation in this article is used to describe only the physical factors, which contribute to the retirement of fixed assets from use. The term obsolescence describes the functional or intangible factors that cause the permanent abandonment of fixed assets. Fixed assets are considered to be obsolete if they go out of use before the end of their potential physical life, because of changing economic or technical conditions. Depreciation, then, implies the gradual expiration or consumption of productive power, while obsolescence implies the abandonment of unused potential productive power. The difficulties of separating physical depreciation and obsolescence, the two dissimilar things may be too great to attempt at the present time, but accountants should recognize that they are different in nature, and that considerable progress in predicting obsolescence has been made in the past and may be expected to be made in the future.